Evaluation of the compromise between harmonic distortion and energy efficiency in the power factor improvement systems of the Zeta, Luo and Cuk feeders for brushless DC motors - Ruiz Sarzosa , Saúl Eduardo; Rengifo Rodas , Carlos Felipe; Franco Mejía, Édinson (I+ T+ C- Research, Technology and Science, 2017)
The objective of this article is to evaluate the existing compromise between the harmonic distortion and the energy efficiency of the drivers for brushless DC motors based on the isolated Zeta, Luo and Cuk converters to determine the advantages and contributions of each converter with respect to the energetic efficiency, also, the relation that has this efficiency with the quality of the electrical energy. In order to carry out the proposed evaluation, the inverter models found in the literature were used, as well as the inverter and motor simulation models found in the Simscape Electronics tool of the Matlab software. The research focused on comparing the power factor, total harmonic distortion (THD) and energy efficiency (understood as the quotient between the active energy consumed by the motor and the active energy delivered by the AC network) of a feeder system for a BLDC motor. To make the comparison, two performance criteria were defined based on the simulation of the system with the converters in ideal mode and in real mode. From the experimental tests it was observed that as the energy efficiency of the system increases, the THD increases and the power factor seen by the AC network decreases. From the work it was concluded that the Luo converter is the one that presents the best compromise between harmonic distortion and energy efficiency